Rural Capitalization and Agrarian Transformation in the Ciwidey Highlands, West Java, Indonesia - Hafid Setiadi; Nurrokhmah Rizqihandari; Adhit Setiadi; Ghilman Ismail Fikri; Satria Indratmoko (Journal of Regional and City Planning, 2022)
The objective of this study was to examine the relationship between capitalization and rural transformation. By conducting a study in the Ciwidey Highlands of West Java, this study focused on the development of tourism as a path for capital flow that is directly connected with the existence of agricultural land and the livelihoods of the population as farmers. These two aspects are key elements in reviewing rural transformation. The data for this study were obtained through field observation at fourteen locations of agricultural land and a questionnaire survey distributed among ninety tourism workers. Through map interpretation and descriptive analysis, the results of this study show the impact of capitalization through tourism development in the increasing economic value of land, which results in the desire of farmers to sell their agricultural land. This impact was also seen in the shift in livelihoods. Rural capitalization through tourism investment has a significant impact on livelihoods, land tenure, and land use.